Clinical Characteristics of Pediatric Pyelonephritis Without Pyuria or Bacteriuria. Issue 5 (May 2020) - Yokoyama, Tadafumi; Takemura, Yuta; Irabu, Hitoshi; Taniguchi, Chihiro; Jinkawa, Asumi; Yamamiya, Mari; Obata, Misato; Miyashita, Kengo; Inoue, Mika; Sakazume, Shinobu; Ohta, Kazuhide
Abstract : Background: The gold standard for the diagnosis of acute pyelonephritis (APN) in children is the finding of both pyuria (P) and bacteriuria (B); however, some APN patients have neither of these findings [APN(P(−);B(−))]. Methods: In this study, we investigated APN patients who visited our hospital over 14 years to identify specific clinical characteristics of APN(P(−);B(−)). Results: A total of 171 APN patients were included in the study, and of these 29 were APN(P(−);B(−)). Of the APN(P(−);B(−)) patients, 25.9% had vesicoureteral reflux (VUR), the same percentage as the APN(P(+);B(+)) patients, and 69.0% of APN(P(−);B(−)) patients had already taken antibiotics before diagnosis. APN(P(−);B(−)) patients were older and had a longer duration between onset of fever and diagnosis than the patients with pyuria and/or bacteriuria. In addition, they showed higher C-reactive protein levels. APN(P(−);B(−)) patients had high levels of urinary α-1 microglobulin and urinary β-2 microglobulin. Conclusions: APN is difficult to diagnose in febrile patients who display neither pyuria nor bacteriuria, but as these patients have the same risk for VUR as APN patients with pyuria and bacteriuria, a detailed history establishing the clinical course as well as urinary chemistry investigations, may assist in diagnosis. Abstract : Supplemental Digital Content is available in the text.